Static Analysis of Circular Cylindrical Shell Under Hydrostatic and Ring Forces (Journal of Science and Technology, 2016)
Analysis of circular cylindrical shell under the action of hydrostatic and stiffening ring forces is carried out in this work. The differential equation of equilibrium, similar to that of beam on elastic foundation, was obtained from static principles on the assumptions of P. L. Pasternak. The initial value method was used to solve the obtained fourth order differential equation for both cases of hydrostatic and ring forces. Combined actions of hydrostatic and ring forces were studied as the location of the ring was varied along the height of the reservoir. It appears that the most favourable location for the ring is 2/3 of its height measured from the top. Bending mo-ment, shear force and hoop tension diagrams, essentially necessary for design of the reservoir, were plotted under the action of these forces.